2018
DOI: 10.1186/s12885-018-4806-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers: paving stones on the road towards the personalized precision medicine for oral squamous cell carcinoma

Abstract: Traditional therapeutics have encountered a bottleneck caused by diagnosis delay and subjective and unreliable assessment. Biomarkers can overcome this bottleneck and guide us toward personalized precision medicine for oral squamous cell carcinoma. To achieve this, it is important to efficiently and accurately screen out specific biomarkers from among the huge number of molecules. Progress in omics-based high-throughput technology has laid a solid foundation for biomarker discovery. With credible and systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 164 publications
(161 reference statements)
0
19
0
1
Order By: Relevance
“…At present, there are few biomarkers or targets for OSCC diagnosis and treatment. Therefore, identifying genes which have different expression patterns in OSCC tumors and normal tissues should help elucidate the pathogenesis of OSCC and may provide useful diagnostic biomarkers and therapeutic targets for OSCC treatment [40].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are few biomarkers or targets for OSCC diagnosis and treatment. Therefore, identifying genes which have different expression patterns in OSCC tumors and normal tissues should help elucidate the pathogenesis of OSCC and may provide useful diagnostic biomarkers and therapeutic targets for OSCC treatment [40].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers refer to "biomolecules identified in blood, other body fluids, or tissues that indicate normal or abnormal processes, conditions, or diseases, and can be used to observe the body's response to treatments for diseases or conditions" [121]. Studies have investigated the use of nucleic acid and protein changes in saliva, blood, and tissue samples as biomarkers to improve the diagnosis and prognosis of OSCC [122]. Numerous studies have demonstrated that the loss of specific chromosomal regions in known or speculated tumor suppressor genes can be used as an early predictor of the subsequent progression of oral precancerous lesions [123].…”
Section: Biomarkersmentioning
confidence: 99%
“…However, research has also reported that the global OC genome is hypomethylated and increasingly hypomethylated in univariate association with tobacco/alcohol history and the malignant stage of the tumor [64,65]. Nevertheless, the individual DNA methylotype maintains translational interest for molecular staging, prognosis and customized management of OC patients [66,67,68,69]. In support of this are the recent results obtained by connecting the alteration of the DNA methylotype of HNC patients with gene expression profiling to screen their biomarker potency [70,71].…”
Section: Epigenetic Regulation Of Melatonin In Oral Cancermentioning
confidence: 99%